Environmental Impact and Nutrient Quality Assessment of the Current Diet in Surabaya, Indonesia. (29th May 2020) - Shields, Angela; El-Abbadi, Naglaa; Adamkiewicz, Gary
Abstract: Objectives: As developing nations' income continue to rise, individuals have greater access to high caloric foods leading to increases in obesity and associated chronic diseases. Indonesia is one of several countries facing this dietary shift, exhibiting one of the highest prevalence rates of overweight/obesity in Southeast Asia. The current diet, mainly driven by increased meat and fish intake, is also associated with increases in environmental impact. Behavior change is necessary in order to shift diets toward more healthy and sustainable consumption. In this report, we analyzed the environmental impact and nutrition quality of the current diet in Surabaya, Indonesia. Methods: We administered a 24-hour dietary recall and supplemental questionnaire assessing preferred diet, food access, diet knowledge, and climate change opinions to 100 participants in Surabaya, Indonesia. We created correlates between the 175 commonly consumed foods reported in the dietary recalls and the 2007–08 National Health and Examination Survey (NHANES). The correlates were analyzed using the Nutrient Rich Foods index (NRF) 9.3 and an aggregate environmental score (EIS) made up of 4 life cycle assessment (LCA) indicators including land and water use, greenhouse gas emissions, and eutrophication. Results: Tofu and tempeh were the only foods that scored above the median in both nutrient quality and environmental impact, indicating a high NRF9.3 and low EIS. Fish and chicken scored above the median in nutrient quality but below the 25 th percentile in environmental impact, while eggs scored below the median in both categories. Rice, the most consumed food, scored below the 25 th percentile in nutrient quality but above the median in environmental impact. Beef consumption is low compared to other sources of protein. Fruit intake is low compared to other food groups while vegetable consumption is moderately high, with both lying above the 75 th percentile in both categories. Conclusions: The results highlight that tofu and tempeh may confer the largest benefits in terms of health and environment. Though chicken and fish exhibit high nutrient quality, increased consumption in place of tofu and tempeh may lead to worsened environmental impacts. Funding Sources: Harvard T.H. Chan School of Public Health Rose Service Learning Fellowship Grant.